Pembuatan Katalis Heterogen Naoh/Cao/C Dari Kulit Telur Ayam Untuk Produksi Biodiesel Dari Minyak Sawit Off Grade - Hawa, Karfika Ainil; Helwani, Zuchra; Amri, Amun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Eggshell waste was modified by calcination, hydration and dehydration methods. Which were impregnated with activated carbon and NaOH made to be used as heterogeneous base catalysts used off grade palm oil transesterification reactions.The catalyst with the highest activity on production of biodiesel is obtained in the catalyst prepared by calcination temperature of 800 °C and catalyst ratio mass of 7:3 with transesterification reaction conditions of a molar ratio of methanol/oil 6:1, catalyst dosage of 6% by weight, temperature of 70 °C for 3 hours having yield biodiesel results reached 79,08%.Keyword: activated carbon, biodiesel, calcium oxide, catalysts, transesterification.